Moddeling of Loading Rate Effects on Fatigue Crack Growth - K.M. Gołoś; H.P. Stuwe; R. Pippan (Engineering Transactions, 1993)
A mechanical model of fatigue crack growth at low and intermediate ΔK values is presented. In the model the effect of the loading rate on the fatigue crack growth is considered. The localstress and strain are calculated based on the Hutchinson, Rice and Rosengren (HRR) solution. The required data for predicting fatigue crack growth rate can be found in standard material handbooks where cyclic and fatigue properties of the materials are presented.